Factors influencing change in walking ability in patients with heart failure undergoing exercise-based cardiac rehabilitation. (1st October 2018) - Sutherland, Natasha; Harrison, Alexander; Doherty, Patrick
Abstract: Objectives: Exercise-based cardiac rehabilitation (CR) is an effective intervention for patients with heart failure (HF), in which one of the main targets is to increase physical capacity. In the HF population this is traditionally assessed using distance covered during a walking test. This study aims to establish the extent to which change in walking ability, in HF patients attending CR, is determined by patient characteristics and service provision. Methods: The study utilised routine clinical data from the National Audit of Cardiac Rehabilitation to perform a robust analysis. Change, in metres, between pre- and post-CR six-minute walk tests was calculated. Multivariate linear regression models were used to explore the relationship between patient characteristics, service-level variables, and change in metres walked. Results: Complete and valid data from 633 patients was analysed, and a mean change of 51.30 m was calculated. Female gender (−34.13 m, p = 0.007), being retired (−36.41 m, p = 0.001) and being married/in a relationship (−32.54 m, p = 0.023) were all significant negative predictors of change. There was an additional negative relationship with body mass index (BMI) whereby for every unit increase in BMI, predicted change reduces by 2.48 m ( p = 0.006). Conclusions: This study identified significant patient-level characteristics strongly associated with limited improvement in walking ability following CR. Improving physical capacity is a core component of CR, therefore services should aim to account for baseline characteristics identified in this study as part of tailoring the CR intervention around the individual. Pre- and post-CR physical capacity assessments, which constitute minimum standards for CR, are worryingly low and should be given high priority. Highlights: Heart failure patients make mean change of 51 m on post-rehab six-minute walk test. Being female, in a relationship, retired & higher BMI predict reduced change. We should account for baseline characteristics when tailoring rehab to the patient. Higher priority should be given to pre- & post-rehab physical capacity assessments.